ChemInform Abstract: A 1, 3‐Amino Group Migration Route to Form Acrylamidines. Issue 17 (28th April 2014) - Chauhan, Dinesh Pratapsinh; Varma, Sreejith Jayasree; Vijeta, Arjun; Banerjee, Pallavi; Talukdar, Pinaki
Abstract A novel route for the synthesis of acrylamidines by Cu‐catalyzed addition of tosylazide to 1‐aminopropines and subsequent intramolecular addition of nucleophiles to ketenimines with 1, 3‐amino group migration is presented.